(untitled) (Revista Apotheke, 2025)
Can we rehearse new steps through images that reflect and reverberate everyday unnoticed aesthetics? As a critical ethical-political exercise, the essay reports sensitive experiences with Pedagogy students from the curricular component of Philosophy of Education II, from the Education Center of the Paraíba Federal University, through their photographic essays. In the design of the lines of force produced by the cartographic methodology, we understand that the experience in the course enabled a new look at the teaching training of students and promoted active dialogue with the teaching staff involved in the pedagogical process. The suspension of time, provided by the moment of attention and framing of the images, transformed ignored everyday spaces, filling them with an unexpected aesthetic. By rehearsing other possibilities of representation, figuration and enunciation with images, the pedagogy of/with image opens paths for the construction of critical knowledge that, in different languages and materialities, challenges students and educators to share the sensitive. In the essay, we dialogue with theoretical contributions from thinkers who discuss the expressive and educational possibilities opened by images, their tensions and powers.